MENTORSHIP-SCAFFOLDING AS PREDICTOR OF TEACHERS’ JOB PRODUCTIVITY IN SENIOR SECONDARY SCHOOLS IN LAGOS - Opeyemi, Bakreen Muniru; Mohammed, Mubashiru O.B.; Abari, Ayodeji Olasunkanmi; Oluwatosin, Yahya Isiaq (Erudio Journal of Educational Innovation, 2023)
This study examined the mentorship scaffolding as predictor of Teachers’ job productivity in public senior secondary schools in Lagos State, Nigeria. The study adopted descriptive research design. The population of this study comprised of all the 8510 teachers, 652 Vice Principals and 326 Principals in the Public Senior Secondary Schools within the six Educational Districts in Lagos State, Nigeria. A-15 items Mentorship Scaffolding Questionnaire (MSQ) and 20-items Teacher’s Job Productivity Questionnaire (TJPQ) was used to collect data for this research. Using split half method, Cronbach Alpha was used to measure the internal consistency co-efficient of the Mentorship Scaffolding and Teachers Job Productivity questionnaires. The 15 items on Mentorship Scaffolding show 73.1% reliability and the 20 items on Teachers Job Productivity shows 72.2% reliability. Research questions were analysed using mean and standard deviation while the stated hypotheses were tested using Pearson’s Product-Moment Correlation at 0.05 level of significance.